Computer modelling of cable reinforced membranes - Stanuszek, Marek (Computer Assisted Methods in Engineering and Science; Vol 9 No 2 (2002), 2023)
This paper is intended to summarise the actual work in the area of large deformations of tension systems. The previously conducted research [23, 24] adds significant contributions to the understanding of the response· characteristics of pneumatics and suspended membranes with wrinkling allowed. Here the attention will be focused on the applications of the one-dimensional tensioned cable systems. Two- and three-dimensional tensile structures, will be forced to work with compressed members. Since cables can not transmit any compressive forces a verified numerical algorithm, based on the monitoring of the load displacement path is proposed. The special computer code NAFDEM (Nonlinear Analysis by Finite Difference and Element Methods) [13] was adapted to solve undertaken highly nonlinear problems. Calculated results were verified numerically and compared with the solutions obtained by the numerical integration technique.